SEARCHING FOR NEW FLUORESCENT DYES - Konstantinova, Anastasija; Kirilova, Jeļena; Zaičenko, Andrejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Today, luminescent dyes are widely used in medicine and in various industries. Benzanthrone is widely used as a laser dye, fluorescent pigment,as well as various medical examinations, for example, antibodies are labeled with luminescent dyes to detect antigens in cells. Work aim is synthesize new luminescent benzantrone derivatives with benzimidazole and amino acid residues. Reaction ability of 3-N-(2-chloro-acetamido)benzanthrone to replace the chlorine atom with various heterocyclic amines and amino acids was investigated.